Agro-industrial waste seeds from Peruvian Pouteria lucuma as new source of phytosterols - Guerrero-Castillo P. (2021)
Pouteria lucuma fruit is commonly used to prepare desserts, but it is also sold as pulp or flour. Then, huge amounts of its seeds are produced as agro-industrial waste, frequently eliminated. This study aims at analyzing the presence of all metabolites in Pouteria lucuma seed oil (LSO) by GC-MS and GC-FID. Several compounds were tentatively identified, such as fatty acids, fatty alcohols, carotenes, phytosterols and tocopherols from LSO. A representative result was the high amount of β-sitosterol with 851.49 ± 1.29 mg/100 g of LSO, followed by stigmasterol with 75.42 ± 1.02 mg/100 g. Fatty acids with the highest content were oleic acid (13.57 ± 1.50 g/100 g of LSO), 9E-octadecenoic acid (6.85 ± 1.15 g/100 g of LSO), palmitic acid (5.44 ± 1.18 g/100 g of LSO) and stearic acid (2.12 ± 1.03 g/100 g of LSO). Therefore, metabolites tentatively identified in Pouteria lucuma seed oil have been linked to healthy properties based on a high amount of β-sitosterol present. This evidence could determine this agro-industrial waste with having beneficial properties, thus providing great added value.